2020
DOI: 10.1177/1744806920902559
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of microRNA-185 alleviates intervertebral disc degeneration through inactivation of the Wnt/β-catenin signaling pathway and downregulation of Galectin-3

Abstract: Background: Recent studies have found that microRNAs (miRNAs) play a critical role in development and progression of intervertebral disc degeneration. In the present study, we examined the role of miR-185 in nucleus pulposus cell behavior in vitro and the histological changes of intervertebral disc tissue in intervertebral disc degeneration rat models in vivo. Methods: Intervertebral disc degeneration models were developed in Sprague-Dawley rats. Intervertebral disc tissue was collected for histological evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…These expression levels, as well as the activation of the Wnt/ β-catenin signaling pathway, increased even more when miR-185 was inhibited. However, transfection of miR-185 in vitro and injection of miR-185 in vivo attenuated these effects, leading to decreased rates of apoptosis [61]. miR-143-5p, on the other hand, was shown to be upregulated in degenerated NP tissue of rats.…”
Section: Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…These expression levels, as well as the activation of the Wnt/ β-catenin signaling pathway, increased even more when miR-185 was inhibited. However, transfection of miR-185 in vitro and injection of miR-185 in vivo attenuated these effects, leading to decreased rates of apoptosis [61]. miR-143-5p, on the other hand, was shown to be upregulated in degenerated NP tissue of rats.…”
Section: Apoptosismentioning
confidence: 99%
“…The most promising and thoroughly conducted studies investigating the role of miRNAs in IVD degeneration identified miR-185 and miR-143-5p to be associated with apoptosis. Both studies conducted in vivo experiments using DDD rat models established by needle puncture of the NP tissue [61,62]. miR-185 was found to be targeting galectin 3, a β-galactosidase-binding protein involved in apoptosis and the Wnt/β-catenin pathway [63,64].…”
Section: Apoptosismentioning
confidence: 99%
“…Galectin-3 is a versatile protein orchestrating several physiological and pathophysiological processes in the human body [ 6 ]. Previous studies have shown that the expression of galectin-3 is upregulated in the NP cells and inhibition galectin-3 alleviates the spinal cord injury and IDD [ 7 , 8 ]. Cell therapy may be an effective way to repair IDD; as a strong immune suppressor, TGF- β has been shown to inhibit inflammation respond effectively [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The competing endogenous RNA (ceRNA) hypothesis is an important mechanism that allows circRNAs in cancers by sponging microRNAs (miRNAs) to modulate mRNAs [ 24 ]. Increasing evidence shows that the circRNA and miRNA can regulate apoptosis and autophagy of cells [ 7 , 25 , 26 ], including NP cells [ 27 ]. These identified ceRNA interaction aces may be crucial targets for treatment of IDD [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in some patient samples, miR-21 blocks PTEN-mediated autophagy and promotes extracellular matrix (ECM) degradation, thus facilitating IDD progression; in few other cases, miR-21 increases the interleukin (IL)-6 inflammatory response to blunt autophagy [ 43 , 80 ]. Similarly, miRNAs (miR-129-5p, miR-185) blocking other upstream regulators of autophagy, like BECN-1 and GALECTIN-3, are also deemed responsible for IDD in other reports [ 95 , 101 ]. However, proteins directly involved in the autophagy pathway are also regulated by miRNAs in human IDD.…”
Section: Ageingmentioning
confidence: 92%